A frightening complication after TAVI with Portico Valve: A case report of a “frozen” leaflet stuck in the opened position. - Totaro Antonio; Tota Antonio; Pierro Antonio; Ienco Vincenzo; Galluccio Chiara; Testa Nicola; Testa Gianluca; Sacra Cosimo (Romanian Journal of Cardiology)
A stuck leaflet is a rare complication of transcatheter aortic valve implantation (TAVI). It occurs when one of the leaflets in the implanted valve doesn’t open and close properly. This complication can lead to serious health problems, even death.